Direct generation of an optical vortex beam from a diode-pumped Yb:MgWO4 laser. (27th July 2017) - Lu, Jieling; Lin, Haifeng; Zhang, Ge; Li, Bingxuan; Zhang, Lizhen; Lin, Zhoubin; Chen, Yung-Fu; Petrov, Valentin; Chen, Weidong
Abstract: We report for the first time, to the best of our knowledge, the generation of a multi-watt optical vortex beam based on a novel monoclinic Yb 3+ -doped MgWO4 crystal. The robust first-order Laguerre–Gaussian doughnut beam (LG01 ) with high mode purity and good beam quality can be selectively excited without using any intra-cavity handedness-selective element. Our results demonstrate the potential of the Yb:MgWO4 crystal for generation of high-power optical vortex beams from compact solid-state lasers.